Response to treatment with Interferon beta-1a in patients with relapsing-remitting multiple sclerosis - Làzaro Aurelio Vàzquez Gòmez; Carlos Hidalgo Mesa; Yunier Broche Pèrez; Yanet Valdés Morales (Medisur)
Background: multiple sclerosis modifying drugs are intended to reduce the frequency of relapses, delay the progression of disability, as well as the appearance of new lesions in the Central Nervous System. Objective: to determine the early indicators of response to treatment with IFNb-1a. Methods: Observational, analytical longitudinal prospective cohort study in patients diagnosed with multiple sclerosis. Two study cohorts were formed, each with 39 patients. Results: the mean and standard deviation of the expanded disability status scale at 36 months was 2.37 ± 1.86 in the study group and 3.15 ± 2.1 in the control group. In the outbreaks of .13 ± .33 in the study group and in the control group of .41 ± .59. New lesions in T2 after the first 12 months of treatment was 0.90 ± 1.16 for the study group and 1 ± 1.10 for the control. Extended-scale progression of disability status, pretreatment annualized relapse rate, age of disease onset, time since disease progression, and gadolinium-enhancing lesions were significantly associated with the odds ratio of older Probability of non-progression for the study group with respect to the control group for the combined variable progression by extended disability status scale and relapses. Conclusions: early indicators of response to treatment with interferon beta-1a were identified; that help assess the response to treatment early, which has a positive impact on the evolution of the disease.